REMOTE WORK SUSTAINABILITY AND ITS INFLUENCE ON EMPLOYEE ENGAGEMENT AND WORK–LIFE BALANCE - Vera Herlina Mustari; Danar Tri Hartanto; Klemens Mere (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze remote work sustainability and its influence on employee engagement and work–life balance. The transformation of work patterns driven by digital technological advancement and the increasing implementation of flexible work systems has positioned remote work as a long-term organizational strategy. However, sustaining such systems requires attention to employee well-being and organizational effectiveness. This study employs a literature review method by examining various scientific articles, journals, and relevant academic sources related to remote work, employee engagement, and work–life balance. Research data were collected from indexed scholarly publications and analyzed using a thematic analysis approach to identify patterns, relationships, and major findings from previous studies. The findings indicate that remote work sustainability positively influences employee engagement by increasing flexibility, autonomy, and job satisfaction. In addition, remote work systems can improve work–life balance through reduced commuting time and greater flexibility in time management. Nevertheless, challenges such as social isolation, blurred work boundaries, and stress caused by excessive digital connectivity remain significant concerns. Therefore, organizations need to develop effective strategies to support sustainable remote work implementation.